Business incubators in Brazil : main gaps to be explored by academic researchers - Cazeri, Gustavo Tietz, 1977- (2015)
The business incubators have an essential role at any global entrepreneurial ecosystem. Through the support offered to entrepreneurs in terms of infrastructure and management, they reduce mortality risk of startup companies and contribute to better performance of the country's economy. In order to make a contribution to the academia and to business incubators, this paper is primarily engaged in performing a literature review on Brazilian and international academic basis in order to identify which are the main themes of research conducted involving Brazilian business incubators. The results show that most of the themes are associated with the services provision by the incubators and its management; however, there are many gaps yet to be explored by academic researchers, such as internal characteristics or the interrelationship between business incubators and triple helix